Stabilization of Microgrid with Multiple Inverters. Issue 28 (2018) - Sekizaki, Shinya; Matsuo, Kosuke; Nakamura, Yuki; Sasaki, Yutaka; Yorino, Naoto; Zoka, Yoshifumi; Nishizaki, Ichiro
Abstract: Due to rapid penetration of renewable energy sources, power conversion devices such as inverters increase in power system. Multiple inverters in a small scale network can constitute an islanded microgrid in case that they are disconnected from the bulk power system. Although the islanded microgrid operation contributes to enhance resilience of the power system, microgrid consisted of typical inverters with no inertia faces a serious problem from the viewpoint of frequency and synchronization stability. Since the inertia-less inverters synchronize with the grid based on detected phase angle, they cannot generate stable reference frequency independently. In order to achieve reliable microgrid operation by multiple inverters, the inertia indispensable for stable frequency and synchronization should be implemented to the microgrid. We have developed synchronous inverter that has the inertia and plays a quite significant role to realize the stable microgrid operation. The single-phase synchronous inverter (SSI) has flexibility to install additional functions to operate the islanded small scale grid as the single-phase microgrid. In this paper, the frequency stabilization effect of the multiple SSIs on the islanded microgrid is compared with the inertia-less inverters. Numerical simulations verify that the microgrid with the single-phase synchronous inverters can be operated stably.